PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK BSI MOBILE BANKING TERHADAP KEPUASAN NASABAH BANK SYARIAH INDONESIA (Studi : Kota Tasikmalaya Tahun 2023 - Dede Aji Mardani; Dini Apriani aji (LPPM IAIT, 2023)
This study is to analyze the effect of service quality and product quality of BSI Mobile simultaneously on the quality of service and product quality of BSI Mobile simultaneously oncustomer satisfaction of Bank Syariah Indonesia in Tasikmalaya City. The method used In this study the authors used a quantitative approach. quantitative approach. Quantitative method is a research method that can be research method that can be interpreted as a research method based on the philosophy of positivism philosophy, used to research on certain populations or samples, data collection using research instruments, data analysis isquantitative with the aim of testing the hypothesis that has been set. The results of this research This research shows that Bank Syariah Indonesia (BSI) has a positive and significant influence on customer satisfaction. significant influence on customer satisfaction,. Mobile banking service quality Bank Syariah Indonesia (BSI) has a positive and significant effect on customer satisfaction. Bank Syariah Indonesia customers in Tasikmalaya City. Mobile product quality banking of Bank Syariah Indonesia (BSI) has a positive and significant effect on customer satisfaction. on customer satisfaction. It can be said that the quality of Bank Syariah Indonesia mobile banking products (BSI) has a positive and significant effect on customer satisfaction. Bank Syariah Indonesia customers in Tasikmalaya City. So that service quality and product quality simultaneously simultaneously have a positive and significant effect on customer satisfaction of Bank Syariah Indonesia in Tasikmalaya City.Syariah Indonesia in Tasikmalaya City